Phonology of Malay Language in Karimun Regency, Riau Islands - Kustiah, Hariani; Zulaeha, Ida; Mardikantoro, Hari Bakti (Universitas Negeri Semarang, 2020)
The Malay language that is spoken in Karimun Regency is a unique and diverse language. The uniqueness and diversity of the Malay language lies in phonology. The purpose of this study is to analyze the phonological variations and phonological differences of the Malay language in Karimun Regency, Riau Islands. The focused places of this study are located in three districts, namely Karimun District, West-Kundur District and Moro District. This study uses a dialect geography approach and qualitative descriptive. The data were collected by using the listening that is followed by simak libat cakap method, recording, and taking notes technique. The results showed that the Karimun Malay language has phonological variations in the form of vowel and consonant variations. Phonological variations happen due to geographic locations between different observation areas and they are obliviously limited to other regions. The phonological differences of the Karimun Malay language in the three observation places are categorized in speech difference. The results of data calculated is analyzed the phonological dialectometric method of Karimun Malay language in the three observation places is 4-7% in percentage.